Additive Techniques to Refurbish Ni Based Components - Cardozo, Eloisa Pereira; Pardal, Gonçalo Rodrigues; Rios Contesse, Sergio Eduardo; Ganguly, Supriyo; D’Oliveira, Ana Sofia C. M. (My University, 2019)
Abstract The attractiveness of additive techniques to refurbish worn components requires the availability of data from different process. This study correlates two additive techniques, Plasma Transferred Arc (PTA – AM) and Direct Laser Deposition (DLD), using IN 625 wire. Specific features of each technique are discussed regarding their potential use to recover geometry and properties of worn components. Multilayers were processed with each technique on a section of a blade and the interaction between materials together with the effect of post deposition heat treatment were characterized. Results show that there are differences in the final microstructure and in the interaction with the part being refurbished imposed by the additive technique used. Competitive changes can be made by changing the feedstock. PTA-AM using powder material exhibits a microstructure that approaches that obtained in DLD using wire.
Keywords: additive manufacturing; direct laser deposition; pta, inconel 625; refurbishing